SASSIER22: Full‐Waveform Tomography of the Eastern Indonesian Region That Includes Topography, Bathymetry, and the Fluid Ocean. (28th October 2022) - Wehner, Deborah; Rawlinson, Nicholas; Greenfield, Tim; Daryono,; Miller, Meghan S.; Supendi, Pepen; Lü, ChuanChuan; Widiyantoro, Sri
Abstract: We present a new 3‐D seismic structural model of the eastern Indonesian region and its surroundings from full‐waveform inversion (FWI) that exploits seismic data filtered at periods between 15–150 s. SASSY21 —a recent 3‐D FWI tomographic model of Southeast Asia—is used as a starting model, and our study region is characterized by particularly good data coverage, which facilitates a more refined image. We use the spectral‐element solver Salvus to determine the full 3‐D wavefield, accounting for the fluid ocean explicitly by solving a coupled system of acoustic and elastic wave equations. This is computationally more expensive but allows seismic waves within the water layer to be simulated, which becomes important for periods ≤20 s. We investigate path‐dependent effects of surface elevation (topography and bathymetry) and the fluid ocean on synthetic waveforms, and compare our final model to the tomographic result obtained with the frequently used ocean loading approximation. Furthermore, we highlight some of the key features of our final model— SASSIER22 —after 34 L‐BFGS iterations, which reveals detailed anomalies down to the mantle transition zone, including a convergent double‐subduction zone along the southern segment of the Philippine Trench, which was not evident in the starting model. A more detailed illumination of the slab beneath the North Sulawesi Trench reveals a pronounced positive wavespeed anomaly down to 200 km depth, consistent with the maximum depth of seismicity, and a more diffuse but aseismic positive wavespeed anomaly that continues to the 410 km discontinuity. Plain Language Summary: Earthquakes that trigger devastating tsunamis have caused hundreds of thousands of deaths in Southeast Asia in the past two decades. These events are driven by processes in the Earth's interior such as descending (or subducting) tectonic plates. These plates can be imaged using seismic waves generated by earthquakes and recorded at the surface. We have developed a structural image of the Earth's interior beneath the eastern region of Southeast Asia using an advanced imaging methodology, which takes the full physics of seismic wave propagation into account. Its success is strongly dependent on being able to account for potentially complex models of the Earth; here, we investigate the effect of mountain ranges, ocean floor profiles, and the presence of a fluid ocean on the propagation of seismic waves, which are not routinely accounted for in other studies. Our final model reveals several tectonic plates descending down to ∼400 km depth, in particular around Sulawesi (Indonesia) and a collision of two plates south of the Philippines, which results in a reversal of the descent direction. The new images contribute to a better understanding of on‐going processes in the Earth, which has important implications for tracking the evolution of tectonic plates over time, and for assessing earthquake and tsunami hazards. Key Points: Double‐subduction with a polarity reversal near the southern segment of the Philippine Trench is revealed The effects arising from surface topography, bathymetry, and the fluid ocean on synthetic waveforms become pronounced at periods ≤20 s For seismic waves that traverse oceanic regions, ignoring the fluid ocean in waveform predictions can compromise the reconstruction of small‐scale features